Implementasi Bussines Intelligence Dalam Pendukung Keputusan Menentukan Talent Dengan Metode Naïve Bayes - Prahenusa Wahyu Ciptadi (Universitas PGRI Yogyakarta, 2023)
The development of information technology in an organization or company can be used to support a large number of business decisions to be made. The developments that have occurred have made it possible for companies engaged in similar fields to compete for the best talent development results. PT. XYZ is a financial services or training company that has several services such as public training, in-house training and seminars (workshops). There are often difficulties in this industry in increasing the number of applicants to conduct training. An appropriate talent management strategy can increase or maximize the profits earned by the company. This research uses the concept of business intelligence and data mining methods based on talent prospect data for the data analysis process.